2011
DOI: 10.1093/infdis/jir535
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation and Survival of Hepatitis C Virus on Inanimate Surfaces

Abstract: These findings are important for assessment of HCV transmission risks and should facilitate the definition of stringent public health interventions to prevent HCV infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
71
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 38 publications
5
71
0
7
Order By: Relevance
“…Interestingly, the protective effect of organic load for chlorine and peracetic acid inactivation was not observed for another flavivirus (WNV) examined in this study. In this regard, our results with WNV were similar to those described previously for the flavivirus hepatitis C [12]. Doerrbecker et al [12] dried HCV onto stainless steel coupons in the absence or presence of 50% human serum as organic load, and then subjected the virus to a series of alcohols and disinfectant products, including quaternary ammonium compounds and peroxides.…”
Section: Comparison Of Inactivation Efficacy For Zikv Vs Other Flavisupporting
confidence: 86%
See 3 more Smart Citations
“…Interestingly, the protective effect of organic load for chlorine and peracetic acid inactivation was not observed for another flavivirus (WNV) examined in this study. In this regard, our results with WNV were similar to those described previously for the flavivirus hepatitis C [12]. Doerrbecker et al [12] dried HCV onto stainless steel coupons in the absence or presence of 50% human serum as organic load, and then subjected the virus to a series of alcohols and disinfectant products, including quaternary ammonium compounds and peroxides.…”
Section: Comparison Of Inactivation Efficacy For Zikv Vs Other Flavisupporting
confidence: 86%
“…In this regard, our results with WNV were similar to those described previously for the flavivirus hepatitis C [12]. Doerrbecker et al [12] dried HCV onto stainless steel coupons in the absence or presence of 50% human serum as organic load, and then subjected the virus to a series of alcohols and disinfectant products, including quaternary ammonium compounds and peroxides. The data indicated that the human serum did not confer resistance to alcohols and other biocides tested for HCV.…”
Section: Comparison Of Inactivation Efficacy For Zikv Vs Other Flavisupporting
confidence: 86%
See 2 more Smart Citations
“…Different studies have recently evaluated the environmental stability of HCV and its susceptibility to chemical biocides in quantitative suspension assays (15)(16)(17)(18)(19) or on dried surfaces (20,21). However, virus inactivation mechanisms of these and other procedures and the question of which parts of the virus particles are specifically disrupted have not been addressed.…”
mentioning
confidence: 99%